Synthesis and Characterization of Azo Dyes Ligands Complexes with Rh (III) and La (III) and Studies Their Industrial and Bacterial Application - Amer. J. Jarad (Journal of Global Pharma Technology, 2019)
1-[4-(2-Hydroxy-4, 6-dimethyl-phenylazo)-phenol]-ethanone (HL1) and 2-(4-methoxy-phenylazo)-3, 5-dimethyl-phenol (HL2) were produced by combination the diazonium salts of amines with 3, 5-dimethylphenol. The geometry of azo compounds was resolved on the basis of (C.H.N) analyses, 1H and 13CNMR, FT-IR and UV-Vis spectroscopic mechanisms. Complexes of La (III) and Rh (III) have been performed and depicted. The formation of complexes has been identified by using elemental analysis, FT-IR and UV-Vis spectroscopic process as well, conductivity molar quantifications. Nature of complexes produced have been studied obeyed mole ratio and continuous alteration ways, Beer's law followed through a concentration scope (1×10-4 - 3×10-4 M). High molar absorbtivity from the compound solutions were noticed. Analytical data showed that all the complexes offered 1:3 metal-ligand ratios. In the radix from physicochemical datum an octahedral structure was described of the complexes. Biological activity of these compounds was assayed. Other than, the dyeing carried out of the produced compounds was practical in cotton fabric. The dyes were checked into light and detergent firmness. Keywords: Complexes, Azo dyes, Biological activity, Acetophenone, Aniline.